2014
DOI: 10.3390/molecules19021651
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Inflammatory Markers of Atherosclerosis and Carotid Intima-Media Thickness in Obstructive Sleep Apnea

Abstract: Obstructive Sleep Apnea (OSA) is a sleep-related breathing disorder associated with the development of cardiovascular diseases and atherosclerosis. Systemic inflammation plays an important role in the development of cardiovascular complications in OSA patients. The aim of the study was to evaluate the relationship between carotid intima-media thickness (cIMT) and inflammatory markers plasma levels in OSA patients. We enrolled 80 OSA patients and 40 controls matched for age and body mass index (BMI). The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
79
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 54 publications
8
79
1
2
Order By: Relevance
“…In one study of 102 Turkish patients [22], the walls of the CCA were thicker and the intima-media thickening ratios were higher in patients with severe OSAHS than in patients with mild-moderate OSAHS. Ciccone et al [23] found, in a study of 80 Italian patients, that the carotid IMT was higher in OSAHS patients than in control subjects, and that moderate-severe OSAHS patients had a significantly higher carotid IMT than patients with mild OSAHS. Fox et al reported that Canadian OSAHS patients, who did not have a history of additional risk factors for cardiovascular disease, had a higher carotid IMT than individuals in a BMI-, age-and gender-matched community-based cohort [24].…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 102 Turkish patients [22], the walls of the CCA were thicker and the intima-media thickening ratios were higher in patients with severe OSAHS than in patients with mild-moderate OSAHS. Ciccone et al [23] found, in a study of 80 Italian patients, that the carotid IMT was higher in OSAHS patients than in control subjects, and that moderate-severe OSAHS patients had a significantly higher carotid IMT than patients with mild OSAHS. Fox et al reported that Canadian OSAHS patients, who did not have a history of additional risk factors for cardiovascular disease, had a higher carotid IMT than individuals in a BMI-, age-and gender-matched community-based cohort [24].…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] CPAP is currently the most effective treatment for reducing associated CVD risks, including blood pressure, atherosclerotic manifestations, [32][33][34] and mortality, 15 in male subjects. The elderly have higher cardiovascular mortality rates, but CPAP may reduce this risk.…”
Section: Discussionmentioning
confidence: 99%
“…The reference value of CRP is <3 mg/L. (25) Angiography is the gold standard for determining the degree of coronary stenosis. The finding of minimal stenosis in one coronary artery, expressed as 0% stenosis, indicates a normal coronary without stenosis.…”
Section: Study Subjectsmentioning
confidence: 99%